Interfering with Autophagy: The Opposing Strategies Deployed by Legionella pneumophila and Coxiella burnetii Effector Proteins - Thomas, David R.; Newton, Patrice; Lau, Nicole; Newton, Hayley J. (Frontiers in Cellular and Infection Microbiology, 2020)
Autophagy is a fundamental and highly conserved eukaryotic process, responsible for maintaining cellular homeostasis and releasing nutrients during times of starvation. An increasingly important function of autophagy is its role in the cell autonomous immune response; a process known as xenophagy. Intracellular pathogens are engulfed by autophagosomes and targeted to lysosomes to eliminate the threat to the host cell. To counteract this, many intracellular bacterial pathogens have developed unique approaches to overcome, evade, or co-opt host autophagy to facilitate a successful infection. The intracellular bacteria Legionella pneumophila and Coxiella burnetii are able to avoid destruction by the cell, causing Legionnaires’ disease and Q fever, respectively. Despite being related and employing homologous Dot/Icm type 4 secretion systems (T4SS) to translocate effector proteins into the host cell, these pathogens have developed their own unique intracellular niches. L. pneumophila evades the host endocytic pathway and instead forms an ER-derived vacuole, while C. burnetii requires delivery to mature, acidified endosomes which it remodels into a large, replicative vacuole. Throughout infection, L. pneumophila effectors act at multiple points to inhibit recognition by xenophagy receptors and disrupt host autophagy, ensuring it avoids fusion with destructive lysosomes. In contrast, C. burnetii employs its effector cohort to control autophagy, hypothesized to facilitate the delivery of nutrients and membrane to support the growing vacuole and replicating bacteria. In this review we explore the effector proteins that these two organisms utilize to modulate the host autophagy pathway in order to survive and replicate. By better understanding how these pathogens manipulate this highly conserved pathway, we can not only develop better treatments for these important human diseases, but also better understand and control autophagy in the context of human health and disease.